2020
DOI: 10.1093/brain/awaa400
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal features of β-γ phase-amplitude coupling in Parkinson’s disease derived from scalp EEG

Abstract: Abnormal phase-amplitude coupling between β and broadband-γ activities has been identified in recordings from the cortex or scalp of patients with Parkinson’s disease. While enhanced phase-amplitude coupling has been proposed as a biomarker of Parkinson’s disease, the neuronal mechanisms underlying the abnormal coupling and its relationship to motor impairments in Parkinson’s disease remain unclear. To address these issues, we performed an in-depth analysis of high-density EEG recordings at rest in 19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 47 publications
3
61
1
Order By: Relevance
“…This could point to a primarily cortical pathology underlying aberrant PAC in OCD. Relevant to this proposal is the recent suggestion that scalp EEG recorded PAC in PD could be a manifestation of the activity of two physiologically distinct oscillators from two spatially distinct cortical substrates [46]. The interpretation of our intracranial analysis is, however, clearly limited by the small sample size and further recordings are required to systematically compare the cortical pattern of PAC to oscillations within the accumbens.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This could point to a primarily cortical pathology underlying aberrant PAC in OCD. Relevant to this proposal is the recent suggestion that scalp EEG recorded PAC in PD could be a manifestation of the activity of two physiologically distinct oscillators from two spatially distinct cortical substrates [46]. The interpretation of our intracranial analysis is, however, clearly limited by the small sample size and further recordings are required to systematically compare the cortical pattern of PAC to oscillations within the accumbens.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta-analysis identified OCD as a possible risk factor for subsequently developing PD [45]. While most studies of PAC in PD patients have exclusively focused on motor cortex oscillations, a recent scalp EEG study with whole-brain source localization demonstrated beta-gamma coupling in dorsolateral prefrontal, premotor cortex, primary motor and somatosensory cortices, greater in the hemisphere contralateral to the clinically more affected side [46]. Aberrant mediofrontal synchronization was not observed in PD [46], pointing to a potential neuroanatomical difference between OCD and PD for a shared underlying neurophysiological abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the KL-MI of the distribution of the average amplitude across phase bins was calculated as described in (Tort et al, 2010), which measures the difference to a uniform distribution. Furthermore, we evaluated PPC for the GPe-p firing rates filtered around f p and f a using the waveform analysis described in (Gong et al, 2020). In short, this method calculates the average waveform of the high-frequency signal, time-locked to the zero-crossing of the low-frequency signal.…”
Section: Spectral Analysismentioning
confidence: 99%
“…In Parkinson's disease (PD), synchronized oscillations have been reported throughout all major BG nuclei (Wichmann, 2019) including the GPe (Wichmann and Soares, 2006;Mallet et al, 2008). These oscillations are characterized by transient power increases in the beta frequency band (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and an increased phase-amplitude coupling between the phase of a beta signal and the amplitude of a high-frequency gamma signal (50-250 Hz) (Jenkinson et al, 2013;Lofredi et al, 2019;Gong et al, 2020). Computational models of BG phase transitions in PD suggest that the GPe is involved in the oscillation generation, either via its recurrent coupling with the subthalamic nucleus (STN) or via its processing of inputs from striatum (STR) (Pavlides et al, 2015;Schroll and Hamker, 2016;Rubin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-frequency coupling between the phase of β oscillations and the amplitude of γ oscillations is widely considered as a pathophysiological biomarker for Parkinson's disease. 1 Recordings via subdural electrocorticography (ECoG), local field potentials (LFP), and even non-invasive EEG revealed enhanced β-γ phase-amplitude coupling (PAC) during the resting state of patients with Parkinson's disease in both cortex [1][2][3] and subthalamic nucleus (STN) 4 , as compared with either healthy controls or patients with non-movement disorders. Exaggerated β-γ PAC at rest in patients with Parkinson's disease has been associated with motor impairment 1,[3][4][5] and can be attenuated by deep brain stimulation of the STN or by dopamine replacement therapy.…”
Section: Introductionmentioning
confidence: 99%